Intracerebral haemorrhage: A rare presentation of phaeochromocytoma - Swati Chhikara; Vijay Kumar; Shrikiran Hebbar; Santosh P Prabhu; Sundeep P Thotan; Suneel C Mundkur (Wolters Kluwer Medknow Publications, 2021)
Phaeochromocytoma is a rare childhood adrenal medullary catecholamine secreting tumour, arising from the chromaffin cells of the sympathetic origin derived from the neural crest cells. Only a few cases have been reported in the literature so far. We report an uncommon presentation in a 5-year-old boy with intracerebral haemorrhage, hemiplegia, and paroxysmal hypertension. Magnetic resonance imaging of the brain showed chronic and acute hemorrhagic infarcts in the left cerebral hemisphere and no vascular anomaly seen on cerebral venogram. Computed tomography scan abdomen showed a mass in the lesser sac and urinary catecholamines were elevated. The patient underwent exploratory laparotomy and the mass was excised in toto. Histopathological examination (HPE) confirmed the diagnosis. This case illustrates the need for keeping in mind atypical presentations of phaeochromocytoma especially in children; as it is a treatable cause of hypertension and early diagnosis with adequate management can prevent morbidity and fatal outcomes.